HISTORICAL PRECONDITIONS OF FLUCTUATIONS IN THE FINANCIAL AND ECONOMIC DEVELOPMENT OF COUNTRIES ACCORDING TO THEIR EXTERNAL ECONOMIC CONDITIONS - KAPITULA, Serhiy; RTYSHCHEV, Serhii; YELIZAROV, Igor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The dynamics of the sex-age structure of the population of Ukraine during 1795-2013 are considered and the overall population growth and its average annual growth rate are analyzed with a breakdown of migration and natural circumstances. It is emphasized that as of 1991, the population of Ukraine was almost 52 million people, and today this value fluctuates around 29 million people, which is due to a number of negative factors, the most acute of which are military actions since the beginning of 2022. The age structure of the population of Ukraine during the specified period is also analyzed. According to statistical data and forecasts, the population of Ukraine will decrease, especially among those of working age. This causes a number of economic and demographic problems that will affect the state of the country’s financial and economic development over the coming decades. Similarly, the sex-age structure of the population of the European Union is analyzed. Despite the absence of a number of negative economic and demographic factors inherent in Ukrainian society today, the European Union also has similar problems with Ukraine in terms of demographic development. It is predicted that by 2100 the population will age and the proportion of people under 60 will decrease compared to 2023. This situation is also significantly influenced by external economic conditions both at the state level and at a more global level. A comparison of the projected population changes in Europe and Africa by 2100 is presented, which demonstrates a significant increase in the population of Africa over the next 75 years. According to the analysis of the data on the forecast of the size of the gross domestic product in the largest economies of the world by 2075, it is concluded that a number of African countries will have a significant increase in a number of economic indicators, the most important of which is the gross domestic product. These changes are justified to a certain extent by changes in demographic indicators, both in terms of the productive workforce and consumers of mass consumption goods. In addition, it was noted that the proportion of young people in a number of African countries is increasing, in contrast to the aging population of Europe, which is also a certain driver of economic growth and improvement of the financial and economic condition of the relevant regions. Based on the data provided, a conclusion was drawn about the significant impact of demographic changes and external economic conditions on the financial and economic state of countries and regions and the need to necessarily take into account changes in population size when making financial and economic calculations and forecasts.